THE ROLE OF ISLAMIC RELIGIOUS COUNSELOR IN THE DEVELOPMENT OF ISLAMIC ARTS IN LANGKAT REGENCY - Lubis, Putri Rahmadhani; Peranginangin, Indira Fatra Deni; Ningsih, Sri (Academic Solution Publisher, 2025)
The development of Islamic art plays a crucial role in religious education and character building for the younger generation. However, the practice and training of Islamic art at the community level still face various challenges. This study aims to analyze the role of Islamic religious instructors as agents of change in developing Islamic art in Batang Serangan District, Langkat Regency. The study employed a qualitative descriptive approach, incorporating in-depth interviews with four religious instructors, complemented by qualitative participatory methods and data analysis. The results indicate that religious instructors actively participate in introducing Islamic art, guiding arts groups, instilling religious and moral values, and increasing community participation in Islamic art activities. These findings emphasize the importance of integrating participatory methods and the active role of instructors as agents of change in cultural transformation and religious education. This research empowers practitioners, historians, and stakeholders to optimize Islamic art training and opens up opportunities for broader, further research combining qualitative and quantitative methods.